Impact of the SARS-CoV-2 pandemic and associated lockdown measures on attendances at emergency departments in English hospitals: A retrospective database study - Steven Wyatt; Mohammed A Mohammed; Elizabeth Fisher; Ruth McConkey; Peter Spilsbury (Elsevier, 2021)
Background: The SARS-CoV-2 outbreak and associated lockdown measures have challenged healthcare. We examine how attendances to ED in England were impacted. Methods: Interrupted time series regression (January 2019 to June 2020) of data from EDs in 41 English NHS Trusts was used to estimate the initial decrease in attendances and the rate of increase following an interruption from 11 March - 7 April 2020, which included the 23 March lockdown in England. Findings: The SARS-CoV-2 interruption led to an initial 51.1% reduction (95% CI 46.3-55.9%) in ED attendances followed by a linear increase in attendances of 3.0% per week (95% CI 2.5-3.5%).  Significantly larger initial reductions were seen in those aged 0-19 years (69.1%), Indian (64.9%), Pakistani (71.8%), Bangladeshi (75.3%), African (63.5%) and Chinese people (74.5%), self-conveying attendees (60.3%) and those presenting with contusions or abrasions (66.9%), muscle and tendon injuries (65.6%), and those with a diagnosis that was not classifiable (72.7%).  Significantly smaller initial reductions were seen in those aged 65-74 years (42.6%), 75+ years (40.1%), those conveyed by ambulance (31.9%), and those presenting with the following conditions: central nervous system (44.9%), haematological (44.0%), cardiac (43.7%), gastrointestinal (43.4%), gynaecological (43.2%), psychiatric (40.4%), poisoning (39.7%), cerebro-vascular (39.0%), endocrinological (36.1%), other vascular (34.6%), and maxillo-facial (19.7%). No significant differences in the initial reduction of activity were seen in subgroups defined by sex, deprivation, urbanicity or acuity. Interpretation: The SARS-CoV-2 outbreak and lockdown substantially reduced ED activity. The reduction varied by age groups, ethnicity, arrival mode and diagnostic group but not by sex, deprivation, urbanicity or acuity. Funding: No funding to declare.